Pengaruh Kualitas Pelayanan, Harga, dan Citra Perusahaan Terhadap Loyalitas Dengan Kepuasan Konsumen Sebagai Variabel Intervening Pada Grab Malang (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Khasanah, Nur Uswatun; Hidayati, Nur; Arsyianto, Muhammad Tody (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine and analyze the influence of Service Quality, Price and Company Image on Consumer Satisfaction at Grab Malang. Knowing and analyzing the influence of consumer satisfaction, service quality, price and company image on loyalty. Knowing and analyzing the influence of service quality, price and company image on loyalty through consumer satisfaction at Grab Malang. The population of this research was students from the Faculty of Economics and Business, Islamic University of Malang, totaling 699 people, while the sample was 87 respondents.Data analysis in this research uses Path Analysis. The research results show that service quality, price and company image influence consumer satisfaction. Consumer Satisfaction and Company Image Influence Loyalty. Service Quality and Price have no effect on Loyalty. Satisfaction is able to mediate the influence of Service Quality on Loyalty. Satisfaction is able to mediate the effect of price on loyalty. Consumer Satisfaction is unable to mediate the influence of Company Image on Loyalty. Keywords: Service Quality, Price, Company Image, Loyalty, Consumer Satisfaction